Study of secondary xylem of six species of the genus Citrus used in Costa Rica. - Brenes-Angulo, Oxana (2012)
Some of the species of the genus Citrus are planted in Costa Rica for fruit production or as shadow trees in coffee (Coffea sp) plantations. However, the exploitation of these plantations is limited only to the fruit, leaving many parts of the tree without a use, which they can be an important biomass source for energy production. In the present work, it was studied the anatomy of the secondary xylem of six species of the genus Citrus: C. aurantifolia (limero), C. limettioides (sweet lemon), C. reticula (tangerine), C. paradisi (grapefruit), C. sinensis (orange) and a variety, C. sinensis var. Washington Navel (hybrid orange) by the anatomical description (macroscopic and microscopic) of their wood, with the aim of providing information for a future process of their trunk’s use. For this, there were taken samples of the trees’ trunks, which were described using international standards of wood description. The results showed that different Citrus species had a dry density wood less than 500 kg/m3, a fine to medium-sized texture, a pale yellow to yellow color, and no veined, flavor or scent. Also, the wood presented diffuse - porous and high abundance of solitary and small pores. There were observed homocellular rays, with a 1-3 cell width and 10-25 cell height. For axial parenchyma, it presented a wide variety of types, ranging from paratracheal to apotracheal, and some parenchyma bands forming false or either annual rings. The presence of traumatic canals and crystals in the species’ wood were also determined. Generally it was evident that the anatomy of the six studied species presented little difference between them, which it is why the difficultness of their possible identification.